Diabetogenic Effects of Parthinium hysterophorous Induced Allergic Rhinitis - Tiwari, Vinita; Singh Parmar, Hamendra (Inflammation & Allergy-Drug Targets (Discontinued), 2012)
Diabetes mellitus (DM) is known to be associated with the cytokines secreted by Th1 cells, while allergic rhinitis (AR) is mainly regulated by Th2 cytokines. According to Th1/Th2 paradigm, there is an inverse relationship between Th1 and Th2 cytokines and resultantly, both the aforesaid diseases are also inversely correlated. On the other hand, numbers of clinical reports suggest every possible correlation between DM and AR including positive, negative and neutral. However, till to date, no experimental report available, suggesting the changes in glucose homeostasis of animal model(s) of allergic rhinitis, if any. Therefore, in the present study we have observed the changes in glucose homeostasis of the animals bearing AR induced by Parthinium hysterophorous (PH). The condition of AR was induced by intranasal instillations of the acetone extract of PH. At the end of experimentation, various parameters for AR and DM were evaluated. A significant increase was observed in total leukocytes in nasal fluid, serum glucose, thyroxine, dyslipidemia and activity of α-amylase, pancreatic lipid peroxidation, serum and pancreatic nitrite with a concomitant reduction in serum calcium, triiodothyronine, hepatic glycogen and activity of phosphoglucomutase. However, serum insulin, TSH, pancreatic calcium and hepatic glucokinase increased non-significantly. Immune cells infiltration and increased intra alveolar space were observed in lungs tissue, while alterations were also observed in pancreas of AR treated animals. The induction of AR led to the diabetogenic changes to rats via exerting multifaceted metabolic defects in the biochemical machinery regulating glucose homeostasis.
Keywords: serum glucose